(untitled) - Bergsman, Steve (Hoboken, N.J., 2006)
Real estate financing lessons from some of the best minds in the business The real estate market is booming, and over the last few years, people have turned to this reliable investment because of its incredible potential. However, real estate investing is a much different beast than buying a home. The objective is no longer real estate for individual use, but to lease the property to others in order to create income. In this follow-up to the widely acclaimed Maverick Real Estate Investing, Steve Bergsman describes in detail various real estate financing methods that can be used for real estate investment success. Each chapter discusses a different financing technique-from first mortgages, equity financing, conduits, and agency loans to low-income housing tax credits, distressed mortgages, and UPREITs-and profiles real estate financing mavericks who have used these techniques to capture huge profits. While advice on real estate financing abounds, Maverick Real Estate Financing offers proven techniques and strategies from some of the best minds in the business including: Edward Lampert, W.P. Carey, and Robert Taubman. Steve Bergsman (Mesa, AZ) is a nationally recognized financial and real estate writer. For the past 20 years, he has been a contributor to many leading publications and regularly writes the "Ground Floor" real estate column in Barron's. He is also the author of Maverick Real Estate Investing (0-471-46879-7).
Keywords: Real estate investment,Real property,Đầu tư bất động sản,Bất động sản; Finance,Tài chính